Endovascular Treatment of Congenital Internal Carotid-Jugular Fistula - Wang, Ming; Fan, Weijian; Mungur, Rajneesh; Gu, Jun; Wan, Shu (Frontiers in Neurology, 2018)
A carotid-jugular fistula is a direct communication between the carotid artery and the jugular vein. Both congenital and spontaneous internal carotid-jugulars are extremely rare. We describe the first case of successful endovascular treatment for a congenital internal carotid-jugular fistula. We reported a 64-year-old woman who presented with a pulsatile mass swelling over the left cervical region and left hemiplegia after cough. Digital subtraction angiography confirmed the diagnosis of left high-flow internal carotid-jugular fistula. The fistula was successfully treated by fractional stent-assisted embolization.